PLACE DEIXIS USED BY FOUR CHARACTERS IN THE MOVIE ENTITLED “HER” - CHRISTINE, VIRGINIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: “Her”, Pragmatics, Deixis, Place Deixis, Reference, Context In this modern era, people can learn a language easily. They can learn a language from magazines, newspaper, advertisement, and many more. By watching a movie, people can also learn a language. In linguistics, especially pragmatics, many writers use movie as their object. The writer conducted a studyof the place deixis in the movie entitled “Her”. There are two problems of the study to be solved namely: (1) what are place deixis used by four characters in the movie entitled “Her”; (2) what are the references of the place deixis used by the four characters in the movie entitled “Her”. The aims of this study are to find out the types of place deixis used by four characters and the references of the place deixis used by four characters in the movie entitled “Her”.  This study uses qualitative research because the data are in the form of words.The data is a movie script of “Her” and the data source is the list of place deixisused by four characters in the movie entitled “Her”. In making the data credibleand dependable the writer used data triangulation which is comparing three theories of deixis from Levison (1983), Yule (1996) and Grundy (2000).There were 13 expressions of place deixis that occurred 37 times used by four characters in the movie entitled “Her”. There were five kinds of context that helped the writer to identify the reference of place deixis used by four charactersin the movie entitled “Her” namely picture, paralanguage, co-text, situation andparticipant.The writer suggests the next researcher who is interested in analyzing deixisanalyze another object such as song lyric, newspapers, magazines, etc, by usingother theories of deixis proposed by other linguists.